Hubungan Kepemimpinan Transformasional dan Transaksional dengan Motivasi Bawahan di Militer - - Wagimo; Djamaludin Ancok (Jurnal Psikologi, 2005)
The  aim  of  this  research  is  to  test  the correlations between leadership variable and followers’ motivation in military. There are several hypothesis’ to be tested in this research. (1) There is a significant and positive  correlation between both transformational leadership and transactional  leadership with  followers’ motivation, (2) There  is a significant and positive correlation between transformational  leadership and  followers’ motivation,  (3)  There  is  a significant and positive correlation between transactional  leadership  and  followers’ motivation, and (4) The correlation between transformational  leadership  and  followers’ motivation  is  stronger  than  the  correlation between transactional  leadership and  followers’ motivation. The  subjects  of  this  research  are  110 members of Indonesian Military (Bintara and Tamtama) who  followed  the  Setukpa  and Setukba Education  in Indonesian National Air Force. This research used 2 kinds of questionnaire. The first is motivation questionnaire, and the second  is  the  leadership  questionnaire. The results supported all of hypotheses of the study; (1) F-reg =24,660; (2) r = 0,559; (3) r = 0,225; (4) r = 0,559. Keywords:   motivation,   transactional leadership, transformational leadership.